Religion and post-migration aspirations: Ethiopian migrants in Canada. Issue 2 (3rd April 2022) - Goitom, Mary; Idemudia, Uwafiokun
ABSTRACT: This paper explores the ways in which, as part of their settlement process, Ethiopian immigrants in Canada (1) draw on religious beliefs, practices, and communities; (2) how they employ the teachings of their faith to advance their well-being; and (3) how these practices pattern their resilience and frame how they articulate – and the methods by which they ultimately achieve – their post-migration aspirations. Findings underscore how religion fashions transnational belonging that allows them to maintain multi-stranded social relations, and how this in turn shapes, maintains, and informs their post-migratory lives. The paper concludes with a discussion of the implications for social work practice.